2002
DOI: 10.1002/jgm.345
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal control of transgene expression in vivo using a heat‐sensitive promoter and MRI‐guided focused ultrasound

Abstract: Heating with MRI-FUS allows a tight and non-invasive control of transgene expression in a tumour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 41 publications
1
54
0
Order By: Relevance
“…Similar promoter characteristics were reported in vivo in a number of organs, such as skin (12), muscle (13), prostate (14), and liver (15), that were genetically modified using either a virus or a plasmid to express a reporter gene under the control of the HSP promoter. Noninvasive in vivo local heating, and thus local activation of gene expression, could be achieved with high-intensity focused ultrasound (HIFU) (15)(16)(17), but a subtle compromise has to be found in the heating strategy, because excessive tissue heating can induce tissue damage and necrosis. Local temperature distribution can be monitored with magnetic resonance temperature imaging (MRI) to evaluate the efficacy of heat-induced gene activation technique as well as safety.…”
mentioning
confidence: 99%
“…Similar promoter characteristics were reported in vivo in a number of organs, such as skin (12), muscle (13), prostate (14), and liver (15), that were genetically modified using either a virus or a plasmid to express a reporter gene under the control of the HSP promoter. Noninvasive in vivo local heating, and thus local activation of gene expression, could be achieved with high-intensity focused ultrasound (HIFU) (15)(16)(17), but a subtle compromise has to be found in the heating strategy, because excessive tissue heating can induce tissue damage and necrosis. Local temperature distribution can be monitored with magnetic resonance temperature imaging (MRI) to evaluate the efficacy of heat-induced gene activation technique as well as safety.…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that 39-43 C should be regarded as an effective hyperthermia range to generate desired treatment effects. [5][6][7][8][9][10][11] The temperature higher than 44 C is reported as a cytotoxic temperature which can make cells undergo coagulative necrosis, while essentially no significant cell death would occur below 41 C even with 1-h exposures. 6,[16][17][18][19] It is understandable that, due to different cell and vessel types as well as particular experimental situations, the lower temperature limit for in vitro cell toxicity and in vivo vascular damage reported in previous literatures might vary between 42 and 44 C. Here, a temperature limit of 44 C is targeted to investigate the approximate DC range for the safe hyperthermia therapy.…”
Section: -mentioning
confidence: 99%
“…These exposures can achieve relatively stable temperature elevation within a hyperthermia range of 39-44 C. 6,7 Numerous research studies and clinical reports support the finding that ultrasound-induced hyperthermia can provide a promising and potentially much safer alternative to conventional ultrasound-based cancer therapy. [6][7][8][9][10][11] Despite growing interest in utilizing pHIFU-induced hyperthermia for cancer treatment, it is also suggested that the elevated temperature at the focus should be restricted to be lower than 44 C to avoid undesirable bioeffects. 5,6 However, most researchers just simply empirically select HIFU parameters for different applications.…”
mentioning
confidence: 99%
“…As it can be applied to thermal ablation, MRI may be useful for guiding and monitoring these procedures. Indeed, promising results have emerged on the MRI monitoring of FUS with heat-activated liposomal agents and heatactivated gene therapy (90,91).…”
Section: Future Development Of Technologymentioning
confidence: 99%